2016
DOI: 10.1519/jsc.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Intended and Perceived Training Load of a Professional Futsal Team Over 45 Weeks

Abstract: The aims of this study were to compare the training load intended by a coach with the training load perceived by the players, over a 45-week professional futsal team season and to compare the variation of session rating of perceived exertion (sRPE) across different periods of the season. Eighteen Brazilian professional futsal players participated in the study. The players' rating of perceived exertion (RPE) and coach's rating of intended exertion (RIE) were collected daily throughout the study. To compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 26 publications
6
41
1
1
Order By: Relevance
“…However, it is likely that the number of players and coaches diverges in player-coach studies in team sports. 8,10,27 …”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that the number of players and coaches diverges in player-coach studies in team sports. 8,10,27 …”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…7 In general, a poor relationship between planned and actual training load is reported with a general tendency of coaches to overestimate training load. [8][9][10] More specific, it appears that coaches underestimate player load in low intensity training and overestimate in high intensity training sessions. 10,11 Knowledge of match exertion can help plan the training sessions but this is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…The high effect size found also stands out, which reveals great probability of this fact to be true for tae-kwon-do male athletes. Studies have pointed to the potentiation of the ability of repeated sprints in athletes after a gradual reduction of the training volume 23,24 . Mujika et al 8 reported that the reduction in the training volume leads to an increase in muscle glycogen stores, which, in turn, increase the time that athletes support being at high-intensity physical exercises.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies have investigated differences between loads planned by coaches and perceived by athletes, which has demonstrated a lack of correspondence between this loads for individual and team sports. [5][6][7][8][9][10][11] In team sports, such as soccer, this inconsistency is even bigger, due to the fact that training load it is harder to control during group exercises. 7 In a study that aimed to examine this relation, over the course of 45 weeks during a season, divided into four periods, has found that sessions with a high demand of the training load, the coach's session ratings of perceived exertion (s-RPE) was overestimated when compared to the athletes' s-RPE, during the four periods of the season.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed differences for light and moderate loads in the preseason period and competitive period 2, respectively. 5 Brink, et al 7 investigated the relation between s-RPE during the competitive season among Under-17 and Under-19 soccer players, and found that these young athletes considered the training harder than the coach (p <0.001), which in turn could promote certain negative adaptations from training. However, more recently Redkva, da Silva, Paes & dos Santos 12 did not found differences in s-RPE between players and coaches (p = 0.70), as well as no statistical differences when comparing the s-RPE prescribed by coaches and perceived by athletes (p>0.05) in the different types of training proposed during the preseason period.…”
Section: Introductionmentioning
confidence: 99%